Characterization and Application of Nanoemulsion in Food Industry: A Review (International Journal of Scientific Research in Science and Technology, 2024)
Nanotechnology is an innovative and transformative field with immense potential to revolutionize the food industry. By enabling the manipulation and assembly of materials at the nanometer scale, nanotechnology provides unprecedented opportunities to enhance the quality, functionality, and stability of food products. This includes improving sensory attributes, shelf life, and bioavailability of functional compounds, particularly lipophilic ones, which are often shindered by low solubility and poor absorption. Nanoemulsions, as a key application of nanotechnology, serve as highly effective delivery systems for bioactive compounds, offering enhanced stability, efficient encapsulation, and improved bioavailability due to their small particle size and high surface area-to-volume ratio. The diverse methods of nanoemulsion preparation, including both high-energy and low-energy approaches, allow tailored production suited to various industrial needs. However, challenges such as scalability and the stability of certain components during processing remain areas of ongoing research. Advanced analytical techniques for characterizing nanoemulsions, spanning separation, physical, and imaging methods, provide critical insights into their properties and performance. These methods ensure that nanoemulsions meet the required standards for functionality and safety. The current development and commercialization of nanotechnology-based food products highlight its growing relevance. By integrating nanotechnology, the food industry can address longstanding challenges, improve health benefits, and create innovative solutions that cater to consumer demands, paving the way for a new era in food science and technology.